The Technology We Exalt Today Is Everyman’s Master - Evan Peters (Washington University Journal of Law & Policy, 2014)
This Note discusses United States v. Jones, in which the Supreme Court unanimously held that the government’s GPS placement on Antoine Jones’s vehicle constituted a search warranting Fourth Amendment protection. This Note evaluates Justice Sotomayor’s desire to modify the third party doctrine, an aspiration brought on by emerging technology. The author traces the Court’s historical development of Fourth Amendment search protection law in the context of emerging technology and considers the role the third party doctrine has played in this development. The Note examines current technology, the government’s attempts to rectify gaps in the law resulting from the third party doctrine, and Justice Sotomayor’s conclusion that it is up to the Court to fix the third party doctrine. In reaching the conclusion that the Supreme Court must reformulate its tests for privacy law, the author considers responses from the academic community to the third party doctrine and analyzes how recent courts have grappled with the third party doctrine in the midst of emerging technology.
Keywords: privacy law; Katz; United States v. Jones; third party doctrine; emerging technology; Fourth Amendment; search protection law; expectation of privacy; false friend; electronic surveillance; electronic monitoring; electronic intrusion; ECPA; SCA; warrantless disclosure; technologically netural